2002
DOI: 10.1016/s0009-8981(01)00809-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA mutations associated with mitochondrial diseases by Agilent 2100 bioanalyzer

Abstract: Background: Molecular analysis of mitochondrial DNA (mtDNA) has provided a final diagnosis for many of the mitochondrial diseases. We evaluated the Agilent 2100 bioanalyzer (Agilent Technologies, Palo Alto, CA) to determine whether the system could replace the conventional restriction fragment length polymorphism (RFLP) analysis by the agarose gel electrophoresis for the detection of the mtDNA mutation. Methods: Three members of a family with MELAS syndrome and four members of a family with MERRF syndrome were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Originally, RFLP had the disadvantage of the possibility of ambiguous bands on gels, but by using the bioanalyzer, accu- (11) found that variations in fragment sizes obtained among bioanalyzer chips were less than 10 bp, and this is in agreement with our finding of a variation of 5 bp or less. By using the data produced following digestion with several enzymes separately, we increased the discriminatory power of the technique.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Originally, RFLP had the disadvantage of the possibility of ambiguous bands on gels, but by using the bioanalyzer, accu- (11) found that variations in fragment sizes obtained among bioanalyzer chips were less than 10 bp, and this is in agreement with our finding of a variation of 5 bp or less. By using the data produced following digestion with several enzymes separately, we increased the discriminatory power of the technique.…”
Section: Discussionsupporting
confidence: 90%
“…Nachamkin et al (16) analyzed the flagellin gene of Campylobacter jejuni but found problems resolving fragments differing by 8 to 20 bp using the bioanalyzer compared to an agarose gel. In contrast, Lu et al (11) studied mutations in human mitochondrial DNA by RFLP and found that the bioanalyzer showed better reproducibility than the conventional method. In this study, we demonstrate that the Agilent 2100 bioanalyzer is a useful tool for obtaining accurate and reproducible-enough sizing of RFLP fragments for molecular typing of S. pneumoniae.…”
mentioning
confidence: 98%
“…The chip is designed for the analysis of DNA fragments ranging from 100 to 7,500 bp in length. The procedure was illustrated in a recent publication (Lu et al 2002). In short, the DNA fragments within each sample are separated and labelled within a proprietary gel matrix containing a fluorogenic dye.…”
Section: Methodsmentioning
confidence: 99%
“…Publication Number 5988-7650EN. 2002) (5), a pool of the RNA samples described above or a single DNA sample (RNA-Seq library pool) was loaded as technical replicates in each well of duplicate chips for all three chip types tested. Library length and RIN were consistent between all chips (Figure 2).…”
mentioning
confidence: 99%